2013
DOI: 10.1007/s13566-013-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia treatment outcomes following Gamma Knife radiosurgery with a minimum 3-year follow-up

Abstract: ObjectiveEffective short-term outcomes have been well documented for trigeminal neuralgia (TN) patients treated with Gamma Knife radiosurgery (GKRS) with reported success rates of 70–90 % with median follow-up intervals of 19–75 months. Fewer series, however, have described uniform long-term follow-up data. In this study, we report our long-term institutional outcomes in patients treated with GKRS after a minimum follow-up of 36 months.MethodsThirty-six consecutive patients with medically intractable TN receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…14,16,21 We did not find an association of pain response with development of new numbness or hypesthesia. In addition, we found that younger age, not older age, 7 was associated with recurrence of pain, but this may reflect lack of long term follow-up, and we will have to continue to study longer term outcomes to confirm this findings. In addition, we did not review location of the GKRS isocenter as a predictor of outcome.…”
Section: Discussionmentioning
confidence: 89%
“…14,16,21 We did not find an association of pain response with development of new numbness or hypesthesia. In addition, we found that younger age, not older age, 7 was associated with recurrence of pain, but this may reflect lack of long term follow-up, and we will have to continue to study longer term outcomes to confirm this findings. In addition, we did not review location of the GKRS isocenter as a predictor of outcome.…”
Section: Discussionmentioning
confidence: 89%
“…Positive predictors before RS are an increased age, 83,121 age more than 70 years, 43,57 and typical pain. 77 Negative predictors before RS include multiple sclerosis, 13,62,76,90,112,137 prior surgery 57,74,82,103,106,132 or ablative procedures, 86,132 an atypical component, 82,118 appearance or aggravation of a sensory deficit, 82 previous MVD, 66,75,120,133 age under 70 years, 132 age under 60 years, 112 distance between the isocenter and the exit of the nerve > 8 mm, 112 and diabetes mellitus. 83 Later pain relief maintenance following RS has been positively associated with new facial numbness 63,106,118,132 and no past surgery 25 and negatively associated with a better initial response.…”
Section: General Aspectsmentioning
confidence: 99%
“…This may be attributed to the lower maximum radiation dose, a patient experience of less intensity, or insufficient follow-up. A recent study by Karam et al [3] evaluated GKRS outcomes in TN patients and noted a significant correlation between age and pain recurrence. They reported an increased likelihood of a favorable outcome in patients >70 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…For higher-risk elderly patients, stereotactic radiosurgery (SRS) offers the least invasive option. Although several studies suggested that SRS is an effective surgical option [3,4], the safety and efficacy of SRS in TN patients at least 70 years of age have not been reported. This study aimed to evaluate the outcomes after one or more SRS procedures in this population.…”
Section: Introductionmentioning
confidence: 99%